Laser doppler vibrometer using acousto optic devices for precision vibration measurement - Krishnan Venkatakrishnan. (2008)
The objective of the contact type acousto optic vibration measurement technique basically is to minimize the error induced in the system due to the environment and the vibration of optical components, not by introducing sensors, but by a common optical path. The common optical path is designed in such a way that the measurement and the reference beams pass not only through the same optical path, but also through the same optical components, thereby addressing a complete compensation of errors due to the environment and the vibration of the optical components without the need of costly and inaccurate sensors.